STRATEGI PENCEGAHAN DAN PENANGANAN PENYEBARAN ALIRAN SESAT DI INDONESIA Studi Kasus di Institut Pertanian Bogor - Furqon Syarief Hidayatulloh (Analisis, 2017)
This research aims to describe preventive strategies and solutions to the spread of cults  or misleading  religious sects  in common universities  (non-religion based universities). Bogor Agricultural university  (IPB) as one of the non-religion,  was selected  as the location of the research. Case study technique was used since the research was qualitative  in nature. The data were collected using interviews,   document  analysis,  and  participatory  observation. The results of the research showed that the preventive strategies over the spread of cults or misleading religious sects in IPB were generally performed through  : (1) formal academic activities  in lectures and tutorials of Islamic religion subject; (2) stadium general;  (3)  weekly  religious  studies  within  campus  mosques; (4)  religious development  within IPB dormitories  for first year students; (5) Tarbawi Forum at Al-Hurriyyah (MTA); (6) religious seminars.